A Study of Demographic profile and Brand Preference Drivers of Entry Level Hatchback Users Segment in Delhi - sani, Alamgir (International Journal of Advanced Science and Technology, 2019)
The hatchback configurations and body types of passenger cars are gaining a lot of traction in terms of their popularity and grabbing the attention and interest of the existing as well as potential passenger car buyers in Delhi. This study was carried out in order to identify and establish the brand disposition of consumers towards the hatchback body types and configuration of different brands in Delhi region. It emerged from the study that a significant number of customers residing in this geographical territory are extremely positively disposed to and strongly inclined towards brand Maruti Suzuki when it comes to entry level hatchback models. It also transpired that the buying decision for these cars are focused more on factors like safety, performance, aesthetic and value for money, which turned out to be the major determinants shaping the buyers’ brand inclinations, as it pertains to entry level hatchbacks. It was conclusively demonstrated by Exploratory Factor Analysis that performance, safety, value and aesthetics, strongly and positively impact the consumer’s satisfaction for hatchback cars. In view of the same , it makes abundant sense for the entry level hatchback manufactures to focus on value added activities to ensure a favourable and improved quality and value perception on the part of the buyers. Because of intense competition in the marketplace, brand owners ought to offer highly competitive price options and affordable cars incorporating the best in terms of quality and least maintenance requirements in the interest of their buyers. Factor of fuel efficiency also needs to be strongly factored into by the companies, since it happens to have a very strong and distinct bearing on the consumers’ choices. The brand owners ought to consider these factors as core, since Indian consumers are considerably more pre-disposed and inclined to assign significant weight to these variables at the stage of pre-purchase processing and decision-making, while buying entry level hatchbacks. Keywords: Hatchback, Consumer preference, value for money, value perception, brand disposition.